Advancing Payment Reform at the Community Level. Issue 2 (April 2016) - McHugh, Megan; Shaw, Bethany; Wolf, Laura; Bleser, William; Duckett, Philethea
Abstract : Background: Multistakeholder alliances—groups of payers, purchasers, providers, and consumers that voluntarily work together to address local health goals—have increasingly been used to improve health care quality within their communities. Under the Robert Wood Johnson Foundation's Aligning Forces for Quality (AF4Q) initiative, 16 multistakeholder alliances were charged with advancing payment reform as part of a larger effort to achieve dramatic and sustainable quality improvement. Methods: Drawing upon key informant interviews with alliance leaders and document reviews conducted from 2010 to 2014, we describe the payment reform projects undertaken by the AF4Q alliances and the roles that the alliances played to advance them. Results: The most common types of projects pursued by alliances were those that introduced supplemental payments to fee-for-service reimbursement and built upon alliances' ongoing quality improvement initiatives. Alliances advanced payment reform through 4 roles: (1) educating and advocating, (2) designing payment reform projects, (3) recruiting participants, and (4) supporting the operation of projects. However, less than half of alliances' payment reform projects were operational by 2014. Conclusions: Quality improvement–focused multistakeholder alliances may play meaningful roles to advance payment reform, but they are not a panacea for overcoming well-documented barriers to reform.